Clinical phenotype and genotype of children with GABAA receptor α1 subunit gene-related epilepsy - Zhang, Linlin; Liu, Xinjie (Frontiers in Neurology, 2022)
Objective: This study aimed to summarize the clinical phenotype and genotype of children with epilepsy caused by GABRA1 gene variants. Methods: Eight epilepsy patients, who were admitted to Qilu Hospital of Shandong University from 2015 to 2021, were enrolled in the study. GABRA1 gene variants were detected by whole-exome sequencing. Epilepsy clinical manifestations, electroencephalography, neuroimaging characteristics and treatment methods were retrospectively analyzed. Results: Among the eight patients, four were males and four were females. Epilepsy onset age was between three to eight months of age. Two patients had a family history of epilepsy. Six cases were de novo variants, and two were hereditary variants. Two children carried the same pathogenic variants, and five carried novel pathogenic variants that had not been reported internationally. The types of seizures were diverse, including focal seizures in five cases, generalized tonic-clonic seizures in five cases, and spasms in two cases. Electroencephalography of seven cases showed abnormal background rhythms, and six cases showed abnormal discharge during the interictal period. No obvious abnormalities were found on magnetic resonance imaging in five cases. All eight children had different degrees of developmental retardation. Conclusion: De novo pathogenic variants in GABRA1 are more common than inherited pathogenic variants, and most epilepsy symptoms begin in the first year of life, manifesting with a variety of seizure types and developmental delays. Conventional treatment usually involves one or more drugs; although drug treatment can control seizures in some cases, cognitive and developmental deficits often exist. The five newly discovered pathogenic variants enrich the GABRA1 gene pathogenic variant spectrum.